Dynamics of rotating fluids - Davidson, P. A. (New York : Oxford University Press, 2024)
"This is a textbook on rotating fluid dynamics, aimed primarily at graduate students in geophysics, applied mathematics and engineering science. However, it also serves as a reference text for professional researchers in geophysics and related fields. The book combines a deep but broad theoretical foundation with a description and analysis of many of the fascinating examples of rotating flows found in nature. The book is self-contained, starting in Part I with introductory chapters on fluid dynamics and waves. The largest section of the book is Part II, where a broad theoretical framework is developed for rotating flows, including Ekman layers, inertial waves, Taylor columns, Rossby waves, precession, instabilities, rotating convection, vortex breakdown, and rotating turbulence. The book ends, in Part III, with an analysis of some naturally occurring rotating flows, including tornadoes and dust devils, tidal vortices, tropical cyclones, convection in planetary cores, zonal winds in planetary atmospheres, and astrophysical accretion discs"--
Includes appendix and subject index
Keywords: Rotating fluids; Inertial waves; Ekman boundary layers; Geophysical fluid dynamics